2021
DOI: 10.1108/bfj-01-2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability reporting in food industry: an innovative tool for enhancing financial performance

Abstract: PurposeThis study investigates the relationship between the level of sustainability reporting and Food Industry Performance (operational, financial and market).Design/methodology/approachUsing data culled from 1426 observations from 31 different countries for ten years (2008–2017), an independent variable derived from environmental, social, and corporate governance (ESG) score is regressed against dependent manufacture performance indicator variables [return on assets (ROA), Return on Equity (ROE) and Tobin’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 121 publications
1
10
0
4
Order By: Relevance
“…We found that mandatory non-financial disclosure can affect several dimensions of financial performance differently. We showed a general and positive direct effect of mandatory non-financial disclosure on operating profitability, shareholders' returns and returns on sales thus reinforcing and extending Buallay (2022b) and Goel (2021) findings. Nevertheless, the regulation on non-financial disclosure negatively moderates the relationship between sustainability issues and OROA , ROE and ROS.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that mandatory non-financial disclosure can affect several dimensions of financial performance differently. We showed a general and positive direct effect of mandatory non-financial disclosure on operating profitability, shareholders' returns and returns on sales thus reinforcing and extending Buallay (2022b) and Goel (2021) findings. Nevertheless, the regulation on non-financial disclosure negatively moderates the relationship between sustainability issues and OROA , ROE and ROS.…”
Section: Discussionsupporting
confidence: 85%
“…Focusing on the dependent variable side, we used Operating Return on Assets ( OROA ) , Return on Equity ( ROE ), Return on Sales ( ROS ) and Cost of Debt as dependent variables in line with prior scholars' insights (e.g. Buallay, 2022b; Cupertino et al ., 2022a; Goel, 2021). We included different predictors in our analysis to examine the effects of non-financial disclosure regulation and corporate sustainability on distinct companies' financial dimensions related respectively to the standpoints of managers, shareholders, customers and debtholders.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, as highlighted Misra and Mention (2022), the agri-food industry comprises complex value chains and networks consisting of input, production, processing and output stages. Of the eight articles in this special issues, one study addresses the intra-organizational level (Palumbo et al , 2022), and five studies mainly address the organizational level (Buallay, 2021; Dias et al , 2022; Rialti et al , 2022; Penco et al , 2022; Venturelli et al , 2022). The bias toward the organizational and inter-organizational level of analysis seems to mirror the general focus of agri-food industry OI-oriented research.…”
Section: The Future Direction Of Oi Research In the Agri-food Industrymentioning
confidence: 99%
“…Accordingly, additional value can be obtained through tailored human resourced practices and multidirectional knowledge transfer aimed toward long-term strategic partnership (Mahdad et al , 2020; Palumbo et al , 2022). Moreover, the food sector has the capacity to bend the curve on sustainability, downsize the environmental deprivation (Buallay, 2021) and provide responses in societal crisis such as, for example, the COVID-19 pandemic (Penco et al , 2022). Thus, policymakers are encouraged to foster R&D programs and enhance innovation networks (Dias et al , 2022).…”
Section: The Future Direction Of Oi Research In the Agri-food Industrymentioning
confidence: 99%
“…These steps will empower the business enterprise for preparing itself to face the future risks and challenges. Buallay (2021) studied the association between the sustainability reporting and the food industry's operational, financial and market performance. As per this empirical research, there exists a significant relationship between the sustainability reporting and the financial performance (ROE).…”
Section: Review Of Literaturementioning
confidence: 99%